ANALISIS KONSEP ARSITEKTUR NEO-VERNAKULAR PADA PERANCANGAN MALL PELAYANAN PUBLIK DI JEPARA - Rizqi, Muhammad (JIAA: Journal of Islamic Art and Architecture, 2024)
Neo-vernacular architecture is a movement that developed during postmodernism, an architectural movement that emerged in the mid-1960s. Postmodernism emerged in connection with the protest of modernist architects against monotonous models (block-shaped buildings), which were believed to have no character that could distinguish buildings from other buildings. The method used in this research is a qualitative method with descriptive analysis. In this case the application of neo-vernacular architecture in the construction of the Public Service Mall Building "MPP" in Jepara Regency is by applying the joglo roof of the Astana Sultan Mosque building which has a mixed architectural style of Hindhu-Buddhist, Javanese and Chinese cultures combined with motif ornaments from troso blangket batik which is also one of the characteristics of Jepara Regency itself. On the other hand, the main building of the Public Service Mall is inspired by the means of transportation "Ship" which describes most of the Jepara people as fishermen. The design of the Public Service Mall "MPP" in Jepara Regency through the Neo-vernacular Architecture approach aims to provide more optimal services for the community and is also expected to be used as one of the solutions to maintain and preserve local cultural patterns in an increasingly modern era in all aspects, especially in terms of infrastructure so as not to be eroded by the times and lost to oblivion in the future